Wideband CDMA network sensitivity function. - Glisic, S. (IEEE Journal on selected areas in communications)
We analyze capacity losses in code division multiple access (CDMA) networks due to imperfections in the operation of the system components. The main result of this work is a systematic mathematical framework for capacity evaluation of CDMA-based networks in fading channels. This should be considered as an alternative tool to extensive simulations being used for these purposes at the moment. The intention is to provide simple approximate relations that simultaneously take into account: multiple access intracell interference (MAI), intercell interference, and near-far effect, including different sources of power control imperfections. In addition to this, the efficiencies of the major receiver components are also included in the analysis. A flexible complex signal format is used which enables us to model at currently interesting proposals for wideband CDMA (W-CDMA) standards. The theory is general, and some examples of practical set of channel and system parameters are used as illustration. Further elaboration of these results, including extensive numerical analysis based on the offered analytical framework, would provide enough background for the understanding of W-CDMA system performance in a realistic environment